Pendampingan Pemasaran Digital Branding Bagi UMKM Di Desa Candi Kecamatan Bandungan Kabupaten Semarang - Sri Sukaesih; Festy Afifa Afra Maurellita; Evi Rohmiyati; Chintya Asti Halizha; Misael Vicels Ve (Jurnal Bina Desa, 2026)
UNNES GIAT is a student activity in implementing Pancasila in the community. This activity is focused on solving problems in the economic field related to MSMEs in villages that play a major role in driving village economic growth. The challenge faced is the difficulty of competing with business actors who are more adaptive to digital technology. The purpose of this community service is as a step in improving the skills and awareness of MSME actors, especially the use of digital branding as a medium to increase product existence and sales. The method of service is door to door assistance to business actors starting from June 26 - August 17, 2024 to six business actors, namely Arjuna Craft, Lidia Snack & Snack, Rumah Dessert, Nindya Florist, D'Yahya Snack, and Dapur Putri Shima so that the resulting logo, google maps, linktree, and social media for the six MSMEs based on the needs of each business. Digital Branding can help businesses expand market reach, increase operational efficiency, and simplify the marketing process.